Stomatognathic system alterations related to dental and medical practice (2015)
Objectives: To determine the relationship between the alterations of the stomatognathic system (SS) with the use of materials and/or procedures in dental and medical practice Methods: A descriptive, observational and retrospective study was performed with patients from the Dental Clinic (DC) of the Faculty of Dentistry - Universidad Cooperativa de Colombia-Pasto during 2005-2015, corresponding to 3913 clinical records; also patients treated at the Hospital Universitario Departamental de Nariño (HUDN) during 2003-2013, from a database of 3443 medical records. Twenty-five specialists of Dentistry and Medicine were surveyed. Patients with related predisposing diseases and incomplete clinical records were excluded, also specialists who did not sign the informed consent. Alterations were divided in 5 groups: for dental materials; dental and medical manipulation; topical, local and general anesthesia; oral radiology and diagnostic monitoring; and topical treatments with chemicals in the oral cavity. Results: At the DC, 239 patients presented alterations (prevalence= 6.1% CI95% [5,4%-6.1%]), most of them due to materials (like denture stomatitis) and by manipulation (related to dental procedures and use of appliances in the oral cavity, such as contaminated endodontic treatment) ; 27 different alterations were found through dental records and 49 from interviews. At the HUDN, 250 patients presented alterations (prevalence= 7.3% CI95% [6.4%-8.2%]), caused mainly by endoscopy traumas and surgical procedures, mouth abseso, adverse effects to drugs and wounds of the oral cavity were the most common; 34 alterations were found in the medical records and 10 through interviews. Latex, amalgam and sodium hypochlorite are the most common materials that cause alterations of the SS. Conclusions: There is an obvious underreporting that indicates the importance of training professionals who perform procedures where the SS is involved, in order to strengthen this aspect at institutions providing health services and to improve Dental and Medical procedures.